The quality of care and influence of double health care coverage in Catalonia (Spain). Issue 3 (1st September 2000) - Rajmil, Luis; Borrell, Carme; Starfield, Barbara; Fernandez, Esteve; Serra, Vicky; Schiaffino, Anna; Segura, Andreu
Abstract : AIMS: To analyse inequalities by social class in children's access to and utilisation of health services in Catalonia (Spain), private health insurance coverage, and certain aspects of the quality of care received. DESIGN: Cross sectional study using data from the 1994 Catalan Health Interview Survey. SETTING: Child population of Catalonia. PARTICIPANTS: A representative sample of non-institutionalised children younger than 15 years (n = 2433). MAIN OUTCOME MEASURES: Health services utilisation, perceived health, type of health insurance (only National Health System (NHS) or both NHS and private health insurance), and social class. RESULTS: No inequalities by social class were found for the utilisation of health care services provided by the NHS among children in most need. Double health care coverage does not influence the social pattern of visits. Nevertheless, social inequalities still remain in the use of those health services provided only partially by the NHS (dentist) and when characteristics of the last consultation are taken into account. That is, subjects who paid for a private service waited an average of 14.8 minutes less than those whose visit was paid for by the NHS only. CONCLUSION: Equitable access and use of medical care services in relation to need, regardless of the type of insurance and social class of their children and families, has been achieved in this region of Spain; differences by social class remain for those services incompletely covered by national health insurance and aspects of the quality of care provided.